The non-thermal broadband spectral energy distribution of radio galaxies - Romero, Gustavo Esteban (2011)
I present a model for the non-thermal production of electromagnetic radiation in the jets of radio galaxies. The model goes far beyond the simple one-zone models usually applied to these sources. The transport equation is solved in the co-moving frame of the jet, taken into account the inhomogeneous structure of the outflow. Energy distributions for all types of particles are then obtained in a self-consistent way, including protons, electrons, and secondaries. The spectral energy distribution resulting from all relevant radiative processes is computed, including synchrotron radiation, relativistic Bremsstrahlung, proton-proton collisions and subsequent decays, photo-meson production, radiation from pairs formed by photon absorption and injection from decays, as well as direct pair production. Absorbing fields in the host galaxy are considered when computing the final SED. The model is applied to Centaurus A and compared with the available multi-wavelength data.